2017
DOI: 10.1109/tpel.2016.2602243
|View full text |Cite
|
Sign up to set email alerts
|

Self-Learning Direct Flux Vector Control of Interior Permanent-Magnet Machine Drives

Abstract: This paper proposes a novel self-learning control scheme for interior permanent magnet synchronous machine (IPMSM) drives to achieve maximum torque per ampere (MTPA) operation in constant torque region and voltage constraint maximum torque per ampere (VCMTPA) operation in field weakening region. The proposed self-learning control scheme (SLC) is based on the newly reported virtual signal injection aided direct flux vector control. However, other searching based optimal control schemes in the flux-torque (f-t) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The conventional method eliminates the cos( h t) term with the help of the LPF despite of its phase delay. If the two opposite small high-frequency signals about cos( h t) expressed as (17) are virtually injected into the current angle, respectively, the instantaneous input power P ivir2 and P ivir3 can be calculated as (18) and (19) similarly…”
Section: Multiple Signal Inject Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional method eliminates the cos( h t) term with the help of the LPF despite of its phase delay. If the two opposite small high-frequency signals about cos( h t) expressed as (17) are virtually injected into the current angle, respectively, the instantaneous input power P ivir2 and P ivir3 can be calculated as (18) and (19) similarly…”
Section: Multiple Signal Inject Methodsmentioning
confidence: 99%
“…Although the MTPA methods based on signals injection are independent of machine parameters, they would entail the torque ripples and the additional power losses owing to the injection of signals. In order to eliminate these problems in the utilisation of real signal injection, the virtual signal injection methods emerge to enhance efficiency in [16][17][18][19]. When a small high-frequency signal is injected into the measured stator current angle mathematically, there exists high-frequency disturbance in the corresponding calculated instantaneous power.…”
Section: Introductionmentioning
confidence: 99%
“…(6) (7) However, it is highly important to note that even though the machine parameters employed in (6) and (7) are accurate, precise MTPA operation still cannot be achieved. This is due to the neglect of the derivative terms ( , , ) in (5). The influence of these derivatives in (5), namely, , , increases with load or current amplitude .…”
Section: Cosmentioning
confidence: 99%
“…temperature [5]. Therefore, to achieve the accurate MTPA operation is one of the significant challenges associated with the IPMSM control techniques and a large number of studies have been reported in the literature to improve the efficiency of the IPMSM drives.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of research papers have been published to investigate the FW operations of direct torque controlled electric machines [73][74][75][76][77][78][79]. Unfortunately, many of them focus on the field-weakening operation of direct torque controlled induction motors and thus are not readily applicable to the PMSMs [73,77,79].…”
Section: Introductionmentioning
confidence: 99%